(untitled) (Eurasian Journal of Philology Science and Education, 2015)
The semantic types of interrogative sentences with the word "what" have been defined in the article due to the meaning of the predicate and use of interrogative sentences with the word "what". The meaning of the question proper is conditioned by an interrogative semantic element in the semantic structure. Based on this counteracted question forms of seme fall behind in the sentences, and communication and motivation meanings are realized as independent notions. The article highlights the semantic group of self-interrogative sentences with the word ’what’, which provide the basis for the study of semantic types of self-interrogative sentences as pronouns and unpronouns [nemestoimennoy] structure.